2021
DOI: 10.1002/asia.202001342
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Hierarchical Porous Activated Carbon from Banana Leaves for High‐performance Supercapacitor: Effect of Type of Electrolytes on Performance

Abstract: We demonstrate a facile efficient way to fabricate activated carbon nanosheets (ACNSs) consisting of hierarchical porous carbon materials. Simply heating banana leaves with K2CO3 produce ACNSs having a unique combination of macro‐, meso‐ and micropores with a high specific surface area of ∼1459 m2 g−1. The effects of different electrolytes on the electrochemical supercapacitor performance and stability of the ACNSs are tested using a two‐electrode system. The specific capacitance (Csp) values are 55, 114, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
109
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 57 publications
0
109
0
Order By: Relevance
“…Different biomass resources have highly variable compositions and features; therefore, biomass feedstock's characterization is quite important in expressing its suitability for conversion into carbon materials. Various agricultural byproducts, including Albizia procera leaves, [5,10,70] tal palm leaves, [6] Syzygium cumini leaves, [11] Pithophora polymorpha filaments, [7] date palm leaves, [71] banana leaves, [14] nettle fiber clone, [72] and jute, [13,20,73] have been employed as sources for the preparation of low‐cost carbon materials. However, due to eco‐friendly, biodegradable nature, and high carbon and low ash content, enormous research work has been carried out to convert jute into novel carbonaceous materials, including nanocarbon for valuable applications, such as energy storage, sensors, and waste‐water treatment [5–7,11,13,14,20,70,73] …”
Section: Applications Of Jute In Nanotechnologymentioning
confidence: 99%
See 1 more Smart Citation
“…Different biomass resources have highly variable compositions and features; therefore, biomass feedstock's characterization is quite important in expressing its suitability for conversion into carbon materials. Various agricultural byproducts, including Albizia procera leaves, [5,10,70] tal palm leaves, [6] Syzygium cumini leaves, [11] Pithophora polymorpha filaments, [7] date palm leaves, [71] banana leaves, [14] nettle fiber clone, [72] and jute, [13,20,73] have been employed as sources for the preparation of low‐cost carbon materials. However, due to eco‐friendly, biodegradable nature, and high carbon and low ash content, enormous research work has been carried out to convert jute into novel carbonaceous materials, including nanocarbon for valuable applications, such as energy storage, sensors, and waste‐water treatment [5–7,11,13,14,20,70,73] …”
Section: Applications Of Jute In Nanotechnologymentioning
confidence: 99%
“…The development of nanoscale devices has recently become one of the most emerging research areas. Enhancing the surface area of active nanomaterials without increasing the dimensions of the devices leads to more efficient applications in various fields, such as solar cells, sensors, detectors, targeted drug delivery, antibacterial agents, energy conversion and storage, nanogenerators, and catalysis [5–20] …”
Section: Introductionmentioning
confidence: 99%
“…The carbonized product was washed with 0.5 M HCl and DI water and finally dried at 60°C for 24 h to obtain the porous ADCs nanosheets. Similarly, various agricultural wastes have been used for the preparation of efficient ADCs materials, including tal palm leaves (Ahammad et al, 2019a), jam leaves (Deb Nath et al, 2019), bhant leaves (Haque et al, 2020a), rain/monkey pod tree leaves (Khan et al, 2020), rice husks (Haque 2020b), taro stems (Ahammad et al, 2018), Pithophora polymorpha filaments (Shah et al, 2020), banana leaves (Roy et al, 2020), and waste tissue paper scraps (Senthilkumar et al, 2020). Reproduced with permission (Aziz et al, 2017…”
Section: Preparation Of Adcsmentioning
confidence: 99%
“…The resultant composite was used as electrodes for supercapacitors, which exhibited pseudocapacitor behavior and yielded a high areal capacitance of 176 mF/cm 2 at a scan rate of 1 mA/cm 2 with a high specific energy and specific power of 24.5 μWh/cm 2 and 500 μW/cm 2 , respectively. Recently Roy et al (2020) have reported hierarchical porous ADCs for supercapacitor applications. The ADCs were prepared by simple activation of banana leaves with K 2 CO 3 , which produced highly efficient ADCs with a high specific surface area of ~1459 m 2 /g.…”
Section: Applications Of Adcmentioning
confidence: 99%
See 1 more Smart Citation